O jogo teatral na construção de sujeitos - Silveira, Fabiane Tejada da (Universidade do Vale do Rio do Sinos, 2007)
The present study constitutes in a reflection about the emancipatory possibilities of the pedagogical practice carried out in the school through the theather game. Thus, it proposes as its main references the thought of Theodor W. Adorno and Paulo Freire. Furthermore, it promotes the dialog with theorists from the theather-education area, like Richard Courtney, Viola Spolin, Ingrid Kaudela, among others. As empirical base of the reflection were made observations in a group of children and teenagers that were participants in activities done through the theather game in the school, as well as interviews with these students and the teacher. The observations and the interviews were lately analysed by procedures of interpretation philosophically based on phenomenology and hermeutics. The analysis of this material allowed us to conclude that the theather game promoted on the pedagogical scene of the school might proportionate the sensitive development of the student that putting himself in the other’s “role” can i
Keywords: formação; prática pedagógica; teatro; professor; autonomy built; emancipatory pedagogical practice; theather-game; Ciências Humanas